... cin{\acute {e}}tica} }=E_{\mathrm {total} }-E_{\mathrm {reposo} }=\gamma m_{0}c^{2}-m_{0}c^{2}=\left(\gamma -1\right)m_{0}c^{2 ... cin{\acute {e}}tica} }\approx {\frac {1}{2}}\left({\frac {v}{c}}\right)^{2}m_{0}c^{2}={\frac {1}{2}}m_{0}v^{2}} . Como ... cin{\acute {e}}tica} }={\frac {1}{2}}m_{0}v^{2}} . Al expandir γ {\displaystyle \gamma } utilizando una serie de Taylor se ...
displaystyle E_{\mathrm {cin{\acute {e}}tica} }=E_{\mathrm {total} }-E_{\mathrm {reposo} }=\gamma m_{0}c^{2}-m_{0}c^{2}=\left(\ ... displaystyle E_{\mathrm {cin{\acute {e}}tica} }\approx {\frac {1}{2}}\left({\frac {v}{c}}\right)^{2}m_{0}c^{2}={\frac {1}{2}}m ... displaystyle E_{\mathrm {cin{\acute {e}}tica} }={\frac {1}{2}}m_{0}v^{2}}. . ...